Hiv/Aids In Xinjiang: A Serious "Ill" In An "Autonomous" Region - Hayes, Anna (Penerbit Universiti Sains Malaysia (USM Press), 2012)
This paper investigates the sociographic history of HIV/AIDS in the Xinjiang Uyghur Autonomous Region1 in the People's Republic of China (PRC). Xinjiang is China’s largest province and it is located in north-west China. It is home to a number of different minority nationalities as well as increasing numbers of Han Chinese migrants to the region. Xinjiang is also home to a serious HIV/AIDS epidemic and was one of the first areas to be significantly affected by HIV in China. The serious nature of the HIV/AIDS epidemic in Xinjiang, combined with growing concerns by Xinjiang locals that the Chinese government is not doing enough to combat HIV/AIDS among minority nationalities in the region, has the potential to increase regional tensions and provide further fuel to the tinder box that is ethnic relations in Xinjiang. While for the most part, tensions in the region have been focused around separatism and minority rights, HIV/AIDS poses an enormous threat to security within the region due to its ability to strip economic gains and reverse social developments made there over the past few decades and its potential to exact a huge toll in human life. Xinjiang is an important region for China due to both its wealth of natural resources and its strategic capacity as a buffer region between the PRC and Central Asian states. However, an everburgeoning HIV/AIDS pandemic in the region threatens to destabilise China's grand plan for this north-western province if its HIV/AIDS epidemic continues to grow.